Lauric Acid versus Palmitic Acid: Effects on Adipose Tissue Inflammation, Insulin Resistance, and Non-Alcoholic Fatty Liver Disease in Obesity - Viswanathan Saraswathi; Narendra Kumar; Thiyagarajan Gopal; Saumya Bhatt; Weilun Ai; Carmen Ma; Geoffrey A. Talmon; Cyrus Desouza (Biology, 2020)
Coconut oil, rich in medium-chain saturated fatty acids (MCSFA), in particular, lauric acid (LA), is known to exert beneficial metabolic effects. Although LA is the most abundant saturated fatty acid in coconut oil, the specific role of LA in altering obesity-related metabolic disorders remains unknown. Here, we examined the effects of supplementing a high fat (HF) diet with purified LA on obesity-associated metabolic derangements in comparison with palmitic acid (PA), a long-chain saturated fatty acid. Male C57BL/6 mice were fed a control chow diet (CD) or an HF diet supplemented with 3% LA (HF + LA) or PA (HF + PA) for 12 wk. Markers of adipose tissue (AT) inflammation, systemic insulin resistance (IR), and hepatic steatosis, were assessed. The body weight and total fat mass were significantly higher in both HF + LA and HF + PA diet-fed groups compared to CD controls. However, the visceral adipose tissue (VAT) mass was significantly higher (p < 0.001) in HF + LA-fed mice compared to both CD as well as HF + PA-fed mice. Interestingly, markers of AT inflammation were promoted to a lesser extent in HF + LA-fed mice compared to HF + PA-fed mice. Thus, immunohistochemical analysis of VAT showed an increase in MCP-1 and IL-6 staining in HF + PA-fed mice but not in HF + LA-fed mice compared to CD controls. Further, the mRNA levels of macrophage and inflammatory markers were significantly higher in HF + PA-fed mice (p < 0.001) whereas these markers were increased to a lesser extent in HF + LA-fed group. Of note, the insulin tolerance test revealed that IR was significantly increased only in HF + PA-fed mice but not in HF + LA-fed group compared to CD controls. While liver triglycerides were increased significantly in both HF + PA and HF + LA-fed mice, liver weight and plasma markers of liver injury such as alanine aminotransferase and aspartate aminotransferase were increased significantly only in HF + PA-fed mice but not in HF + LA-fed mice. Taken together, our data suggest that although both LA and PA increased AT inflammation, systemic IR, and liver injury, the extent of metabolic derangements caused by LA was less compared to PA in the setting of high fat feeding.